Relationship between Lifestyle and Stress with Hypertension among of Communities in Sigi Regency - Fanny Metungku; Chely Veronica Mauruh; Andi Nur Indah Sari; Niswa Salamung; Uswatun Uswatun (Universitas Bondowoso, 2021)
Introduction : Hypertension is a condition where a person has increased blood pressure above normal or chronic. Peoplecan feels the serious impact of hypertension when complications have occurred. From the results of interviews with 3 respondents with hypertension, said that in everyday life, the diet that is applied is 3 times a day. As for the food they often consume eggs, salted fish, and coconut milk foods. As for the problem of stress, they don't fully understand about stress, it's just that they say they always have a lot of thoughts, irritability, headaches are caused by economic factors. Method: This type of research is analytic research with a cross sectional approach . The sample in this study amounted to 37 people. Meanwhile, the sampling technique was purposive sampling. Results: The results showed that there was a relationship between the style of living with hypertension with a value of p value = 0.041 (> 0.05). There is a relationship between stress and hypertension value p value = 0.045 (> 0.05). From these results, it is suggested that the health center be more active in educating the public about the factors that can trigger hypertension. Conclusion: local health workers always provide education to the public about the factors that can trigger hypertension